2007
DOI: 10.1523/jneurosci.1750-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

PICK1 and Phosphorylation of the Glutamate Receptor 2 (GluR2) AMPA Receptor Subunit Regulates GluR2 Recycling after NMDA Receptor-Induced Internalization

Abstract: Changes in surface trafficking of AMPA receptors play an important role in synaptic plasticity. Phosphorylation of the C terminus of the AMPA receptor (AMPAR) subunit glutamate receptor 2 (GluR2) and the binding of GluR2 to the PDZ [postsynaptic density-95/Discs large/zona occludens-1]-domain containing protein, protein interacting with protein kinase C (PICK1), have been proposed to play an important role in NMDA receptor dependent internalization of GluR2. However, the fate of internalized GluR2 after NMDA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
208
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(230 citation statements)
references
References 27 publications
21
208
1
Order By: Relevance
“…We therefore examined the effects of altered GRIP1-GluA2/3 interaction of three GRIP1 variants (T550M, I586L, A625T) on pH-GluA2 internalization and recycling in live, transfected hippocampal neurons (23). Expression of both WT and GRIP1 variants in neurons mimics the heterozygous state of these variants in individuals with autism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore examined the effects of altered GRIP1-GluA2/3 interaction of three GRIP1 variants (T550M, I586L, A625T) on pH-GluA2 internalization and recycling in live, transfected hippocampal neurons (23). Expression of both WT and GRIP1 variants in neurons mimics the heterozygous state of these variants in individuals with autism.…”
Section: Resultsmentioning
confidence: 99%
“…Taking advantage of the pH difference between extracellular space (pH = 7.4) and intracellular vesicles (pH < 6.0), this assay use a pH-sensitive green fluorescent protein, pHluorin fused to the N terminus of GluA2 (pH-GluA2) as a reporter to visualize the dynamic process of GluA internalization and recycling (22,23). Full details are in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Early studies showed that PICK1 overexpression increases synaptic CP-AMPARs and blocks LTP at CA3-CA1 synapses 92 . In contrast, a subsequent study reported that PICK1 played no role in hippocampal LTP, instead suggesting that it is involved in AMPAR recycling 93 and LTD through promoting the intracellular retention of internalized AMPARs 94 . However, these discrepancies may be explained, at least in part, by the requirement of PICK1 in LTP being dependent on the developmental stage and the induction protocol used 95 .…”
mentioning
confidence: 92%
“…PICK1 besides interacting with GluR2/3 C-terminus also interacts with PKC␣, and it has been proposed that dimeric PICK1 can act to chaperone activated PKC and AMPARs (Chung et al, 2000;Perez et al, 2001). Several studies indicate that PICK1 regulates the surface expression of GluR2 (Perez et al, 2001;Terashima et al, 2004), and it has recently been shown, in a study using pHluorin-tagged GluR2 and fluorescence recovery after photobleaching (FRAP), that the phosphorylation state of GluR2 Ser880 residue, as well as binding of PICK1 to GluR2, regulates the rate of GluR2 recycling to the plasma membrane after NMDA receptor activation (Lin and Huganir, 2007).…”
Section: Ampar Traffic Ampar Biosynthesis and Ampar Interaction Partnersmentioning
confidence: 99%
“…On the other hand, Daw et al (2000) reported that Ser880 phosphorylation can reverse LTD, by disrupting the intracellular retention of GluR2 by GRIP/ABP, and allowing receptors to be delivered to the synapse. The recent study by Lin and Huganir (2007) indicates that the binding of PICK1 to GluR2 regulates intracellular pools of GluR2 in recycling endosomes, that may be regulated differentially in response to different signaling pathways.…”
Section: Role Of Ampars In Ltdmentioning
confidence: 99%